Effects of DA-9701 (motilitone®) on gastric emptying, glycemic control, and oxidative stress in diabetic rats - Minjun Kim; Young Mi Song; Kyung Jae Yoon; Yurim Hong; Jung Ho Park; Yoo Kyung Kim; Juhee Kim; Chong Il Sohn (PLoS ONE, 2025)
Background/aims Diabetes is associated with various gastrointestinal disorders, including altered gastric emptying, which may be rapid, slow, or transient. These alterations can significantly influence gastrointestinal symptoms and directly influence blood glucose levels. DA-9701 (motilitone), a prokinetic agent derived from Corydalis tuber and Pharbitis seed, is employed in Korea to manage functional dyspepsia due to its anti-inflammatory and gastrointestinal motility-enhancing properties. This study aims to investigate the potential of DA-9701 in addressing altered gastric emptying and glycemic control in diabetic rats, thereby validating its broader clinical utility. Materials/methods Diabetes mellitus was induced in rats by streptozocin injection (65 mg/kg, i.p.). Following the onset of diabetes, rats received daily oral administration of DA-9701 for 2 weeks. Gastric emptying rates for liquid and solid meals were measured using plasma acetaminophen levels and residual food mass, respectively. Oral glucose tolerance tests (OGTT), insulin levels, and oxidative stress markers (malondialdehyde [MDA], Ogg1, Gpx, Cat) were assessed. Western blotting and qPCR were used to evaluate the expression of ERK1/2, c-Kit, and proliferating cell nuclear antigen (PCNA) in gastric tissue. Results Diabetic rats exhibited significantly accelerated gastric emptying (liquid GE AUC: + 45.2%; solid GE: + 23.1%, p < 0.01) and elevated blood glucose (327.4 ± 22.8 mg/dL vs. 96.2 ± 10.1 mg/dL in controls, p < 0.001), accompanied by increased oxidative stress markers and expression of c-Kit, ERK1/2, and PCNA. DA-9701 treatment normalized gastric emptying rates (solid GE restored to 55.8%, p < 0.05), reduced MDA, Ogg1, Gpx, and Cat expression, and significantly downregulated ERK1/2, c-Kit, and PCNA. Moreover, insulin secretion increased 2.1-fold in DA-9701-treated diabetic rats (p < 0.05), resulting in improved glucose tolerance (OGTT AUC reduction: −24.6%, p < 0.01). Conclusion DA-9701 normalized gastric emptying and glycemic control while reducing the expression of ERK1/2, c-Kit, and PCNA, which are elevated in diabetic gastric tissues. These findings highlight the dual therapeutic potential of DA-9701 in regulating both gastrointestinal motility and glycemic variability in diabetes, warranting further investigation in clinical settings.